Minor Events and the Risk of Deep Venous Thrombosis - Eekhoff, E. M. W.; Rosendaal, F. R.; Vandenbroucke, J. P. (Thrombosis and Haemostasis, 2000)
Background Deep venous thrombosis is a common disease, with genetic and acquired risk factors. Many patients have a history of minor events (short periods of immobilisation such as prolonged travel, short illness, minor surgery or injuries) before onset of venous thrombosis. However, the role of these minor events has received little formal study. Also, we do not know how minor events might interact with the presence of genetic prothrombotic defects (factor V Leiden mutation, factor II mutation, protein C, S and antithrombin deficiency). Patients and Methods On the basis of case-control data from a thrombosis service in the Netherlands, we added a follow-up period for a casecross-over analysis of minor events as risk factors, and a case-only analysis for the interaction with factor V Leiden. A total of 187 patients with first, objectively diagnosed venous thrombosis of the legs, aged 15–70, without underlying malignancies and without major acquired risk factors entered the study. For the analysis of minor events in the case-cross-over analysis, we used a matched odds ratio; in the caseonly analysis, we used the multiplicative synergy index. Results In 32.6% of the 187 patients with deep venous thrombosis who did not have major acquired risk factors, minor events were the only external risk factors. Minor events increased the risk of thrombosis about 3-fold, as estimated in the case-cross-over analysis (odds ratio 2.9, 95% confidence interval 1.5–5.4). The synergy index between minor events and factor V Leiden mutation in the case-only analysis was 0.7 (95% confidence interval 0.3–1.5). Therefore, persons with factor V Leiden mutation who experience a minor event will have an estimated risk increase of about 17-fold, which exceeds the sum of the individual risk factors. Conclusions Minor events are likely to play an important role in the development of deep venous thrombosis, especially in the presence of genetic prothrombotic conditions.
Keywords: Venous thromboembolism; epidemiology; travel; immobilisation; risk factors; factor V